2007
DOI: 10.1124/dmd.106.012187
|View full text |Cite
|
Sign up to set email alerts
|

Morin (3,5,7,2′,4′-Pentahydroxyflavone) Exhibits Potent Inhibitory Actions on Urate Transport by the Human Urate Anion Transporter (hURAT1) Expressed in Human Embryonic Kidney Cells

Abstract: ABSTRACT:In allopurinol-allergic patients, uricosuric agents are often used in the treatment of hyperuricemia. The existing uricosuric agents are not without problems and the availability of better and safer alternatives is highly desirable. Our previous study (J Pharmacol Exp Ther (2006) 316:169-175) has demonstrated that morin (3,5,7,2,4-pentahydroxyflavone), which occurs in the twigs of Morus alba L. documented in traditional Chinese medicinal literature for treatment of conditions akin to gout, is a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
(46 reference statements)
2
21
0
Order By: Relevance
“…demonstrated that morin inhibited XDH/XO activity in vitro with low micromolar potency . Morin was also shown to inhibit the human URAT1 expressed in human embryonic kidney cells . Moreover, Wang et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…demonstrated that morin inhibited XDH/XO activity in vitro with low micromolar potency . Morin was also shown to inhibit the human URAT1 expressed in human embryonic kidney cells . Moreover, Wang et al .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, some of the renal organic anion transporters were identified in the brush‐border membrane of the proximal tubule in rat kidney and played key roles in mediating renal uric acid excretion, such as GLUT9 (encoded by SLC2A9), URAT1 (encoded by SLC22A12) and OAT1 (encoded by SLC22A6). Mutations in GLUT9 deficiency cause urate reabsorption reduction, resulting in the increased serum uric acid levels and FEUA .…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of flavonoid interactions mediated by ABC transporters seem to be smaller than the CYP‐mediated effects, more specific substrates are needed to understand the results and to establish therapeutic strategies. In combination with metabolism enzymes, several transporters also interact with flavonoids, including uptake transporters (such as organic anion transporter polypeptides (OATPs),157, 158 monocarboxylate transporter 1 (MCT1),159 organic anion transporters (OATS),160 urate anion transporter 1 (URAT1),161 and intestinal facilitated glucose transporter (GLUT2)162 among others).…”
Section: Final Remarksmentioning
confidence: 99%
“…Various constituents of the drug were found to have significant antihyperuricemic potential, including mulberroside A, a stilbene glycoside [21], and a number of flavonoids, primarily morin [22, 23]. …”
Section: Introductionmentioning
confidence: 99%